Total Synthesis of (+)-Kingianin A by Enantioselective Cycloaddition of Strained Cyclobutenone - Zhang, Jie; Yan, Peng; Wang, Zhichao; Zhao, Jinbo; Chen, Qin; Lu, Ping (Synthesis, 2022)
We report here the first asymmetric total synthesis of (+)-kingianin A via dimerization of an enantioenriched bicyclo[4.2.0]octadiene. The synthesis features a chiral oxazaborolidinium ion catalyzed Diels–Alder reaction of strained cyclobutenone and stereoselective functionalization of the cyclobutane ring. A preliminary biological study indicated that (+)-kingianin A exhibits potent anticancer activities.
Keywords: cyclobutenone; chiral oxazaborolidinium ion; Diels–Alder reaction; strain-release driven; bicyclo[4.2.0]octanes; kingianins